Evidence of Quasi-periodic Oscillation in the Optical Band of the Blazar 1ES 1959+650 - Dong, Fu-Tong; Gai, Ning; Tang, Yanke; Wang, Yi-Fan; Yi, Ting-Feng (Research in astronomy and astrophysics, 2022)
We analyzed the optical monitoring data in the R band of TeV blazar 1ES 1959+650 from 2002 to 2018, and provided evidence of a quasi-periodic oscillation in this object. The light curve shows a stable and persistent periodicity at ∼540 days, detected by the Lomb–Scargle periodogram, Jurkevich and weighted wavelet z-transform techniques. The red noise power spectrum was estimated using the PSRESP method, and this period was found to be at >3 σ significance level. There are also two possible periodicities at ∼268 and ∼1100 days detected by all three methods. However, their significance levels are relatively low, and thus these two periods cannot be verified by the present data. We discuss several possible physical models that could explain the periodic variability in this object.